1997
DOI: 10.1074/jbc.272.38.23532
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Animal Cell Mutants Defective in Long-chain Fatty Aldehyde Dehydrogenase

Abstract: Using tritium suicide, we have isolated a variant of the Chinese hamster ovary cell line, CHO-K1, that is deficient in long-chain fatty alcohol:NAD ؉ oxidoreductase (FAO; EC 1.1.1.192). Specifically, it was the fatty aldehyde dehydrogenase component that was affected. The enzymatic deficiency found in this mutant strain, designated FAA.K1A, was similar to that displayed by fibroblasts from patients with Sjö gren-Larsson syndrome (SLS), an inheritable neurocutaneous disorder. Complementation analyses suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 37 publications
1
40
1
Order By: Relevance
“…The extracted lipids were separated with the solvent CHCl 3 /CH 3 OH (9:1). The spots representing underivatized PE and ethanolamine phospholipids with reduced Schiff base (18) were eluted from the silica. Phosphate analysis indicated that 9.1% of the total PE recovered had been reduced by NaCNBH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The extracted lipids were separated with the solvent CHCl 3 /CH 3 OH (9:1). The spots representing underivatized PE and ethanolamine phospholipids with reduced Schiff base (18) were eluted from the silica. Phosphate analysis indicated that 9.1% of the total PE recovered had been reduced by NaCNBH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…FAA.K1B is a variant of CHO-K1 that was isolated from a population of cells that were defective in the ability to take up long chain fatty alcohol (20). All cell lines were routinely cultured in Ham's F12 nutrient mix (BioWhittaker) containing 10% fetal bovine serum (BioWhittaker), glutamine (1 mM), penicillin G (100 units/ml), and streptomycin (75 units/ ml).…”
Section: Methodsmentioning
confidence: 99%
“…After drying, 0.5 ml of 0.5 N NaOH was added to solubilize the cell material at 37°C for 2 h. Aliquots were used for liquid scintillation counting. [9,10-3 H]Hexadecanol into Complex Lipids-FAA.K1B was isolated from a mutagenized population of CHO-K1 that had survived a tritium suicide selection protocol designed to select cells that were less able to take up [9,10-3 H]hexadecanol into stable pools of lipid (20). All, except FAA.K1B, were characterized as having a defect in fatty-alcohol oxidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…[62,63] To date, however, very few studies have focused on the toxic effects of the longer chain aldehydes (C16–C18) that are seen in SLS. [64,65] Because of their lipophilic properties, long-chain aldehydes are expected to partition into membranes of various intracellular compartments, most notably the ER and peroxisomes where FALDH is located.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%